Socialization Of Egg Rendang Making As An Effort To Improve The Nutrition Of The Payolansek Community - Amalina Nur Wahyuningtyas; Novemia Fatrmarischa; Cori Qamara (Jurnal Informasi Pengabdian Masyarakat, 2025)
The goal of this community service project is to improve the Payolansek community's understanding and proficiency in preparing wholesome meals using local ingredients, particularly through the socializing process of creating egg rendang. Since the primary ingredient, eggs, are a cheap and nutrient-dense source of animal protein and the spices employed have a number of health advantages, egg rendang was selected as the activity's focal point. Interactive lectures, demonstrations, and practical egg rendang-making were among the techniques employed. Before and after the activity, questionnaires were used for evaluation. The findings demonstrated that participants' knowledge and proficiency in processing nutrient-dense foods had significantly increased. Additionally, participants were able to make the best use of locally available food components and had a greater understanding of the significance of a balanced diet. It is anticipated that this project will help the Payolansek community's nutritional situation and serve as a template for comparable community service projects in other locations. The success of this activity is aided by the backing of the local village authority.